GREED, OPPORTUNITY, PRESSURE, DAN PENGENDALIAN INTERNAL DALAM KONTEKS FINANCIAL STATEMENT FRAUD - Paturochman, Iwan Ridwan; Nugraha, Cindera Syaiful; Yuliani, Novi Mela (Jurnal Ekonomi Manajemen, 2024)
This study investigates the factors that can trigger financial statement fraud, focusing on four key elements: greed, opportunity, pressure, and the effectiveness of the internal control system in the company. The aim is to obtain empirical evidence regarding the influence of these factors on financial statement fraud. The research employs a descriptive quantitative approach, utilizing primary data collected through questionnaires distributed to employees of PT. BNI Persero, Tbk., Tasikmalaya Branch, using a Likert scale. A total sample of 50 employees who have worked for at least two years was selected through a total sampling technique. Data analysis was conducted using multiple linear regression. The results reveal that greed, opportunity, pressure, and internal control effectiveness simultaneously have a significant impact on financial statement fraud. Partially, greed, opportunity, and internal control effectiveness positively influence financial statement fraud, while pressure has a negative effect.